An application of the ISO/IEC 25010 standard in the quality-in-use assessment of an online health awareness system - Hussain, Azham; Mkpojiogu, Emmanuel O.C. (Penerbit UTM Press, 2015)
Research studies show that there is an upsurge in the number of users surfing the Internet for online health related information.This increase in information seeking behavior on the Web gives rise to the need to ensure that Web based portals meet basic quality in use standards.The ISO/IEC 25010 standard was developed as a model for evaluating such quality in user expectations.In this paper, this standard was used to assess the quality in use of e-Ebola Awareness System, an online health awareness portal. The results provide some insights into the quality into the use of the online portal and also pointing to some issues that impact negatively on the quality in use of the portal, demanding attention and improvement.